Pengaruh Disiplin Kerja, Lingkungan Kerja dan Pelatihan Kerja Terhadap Motivasi Kerja Pegawai Dinas Kearsipan dan Perpustakaan Karanganyar - Budi Santoso, Tomy; Fii Ahsani, Riska (Teewan Journal Solutions, 2025)
This study aims to evaluate the impact of work discipline, working environment conditions, and training programmes on the level of work motivation of employees at the Karanganyar Archives and Library Service. Primary quantitative data is the main source of this research. All employees at the Karanganyar Regency Archives and Library Service constituted the study population, with 57 employees selected as the sample. Data collection was carried out through questionnaires, and data analysis involved multiple linear regression, t-test, F-test, and coefficient of determination. The results showed that work discipline has a significant effect on motivation, work environment has a significant effect on motivation and job training has a significant effect on motivation. The result of the coefficient of determination is 0.828, which means that the influence given by the independent variables, namely work discipline, work environment and job training on the dependent variable of motivation is 82.8% while the remaining (100%-82.8%=) 17.2% is explained by other variables outside the researcher's model.